Desain Website UMKM “Saflorist Padang” Sebagai Media Pengembangan Dan Pemasaran Produk - Anugrah, Intan; Nurul Salma; Rossa Tifana Pratiwi (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
This study aims to design a website for the "Saflorist Padang" UMKM as a medium for digital product development and marketing. In today's digital era, websites function as an important platform to increase market reach, facilitate transaction processes, and strengthen business image. This study uses a descriptive approach with literature study methods, observation, needs analysis, and direct testing of website design. The research sample includes Saflorist owners and employees, customers, potential customers, and web design experts. The results of the study show that a website that is designed responsively, user-friendly, and equipped with e-commerce features can improve operational efficiency and user convenience. The use of SEO optimization techniques has also proven effective in increasing website visibility in search engines, with a 50% increase in traffic after several months. Customers provide positive feedback on the visual design and ease of navigation, as well as the online ordering feature. Recommendations for further development include adding interactive content, developing product personalization features, and strengthening digital marketing strategies through social media and email marketing. In conclusion, this website functions as an effective tool to support business development and online marketing of Saflorist Padang products..